FAKTOR-FAKTOR YANG MEMPENGARUHI KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN (Students' Journal of Accounting and Banking, 2013)
This study aims to analysis the factors affecting the completeness of the disclosure of financial statements in manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study were manufactured companies listed in Indonesia Stock Exchange from 2009 to 2011. The data was analyzed using the multivariate regression. On the hypothesis conducted to identify whether liquidity, leverage, profitability, company size, company ages and public ownership have significant influence towards the level of disclosure of financial statements completeness. The results of the study shows that company size variable, company ages, and public ownership have positive and significant influence towards the level of disclosure of financial statements completeness. The other independent variable such as liquidity, leverage, and profitability do not indicate certain significance towards on the disclosure of financial statements completeness. Keywords: disclosure of financial statements, liquidity, leverage, profitability, company size, company ages, and public ownership.